The Effect of Exogenous Melatonin on the Photosynthetic Characteristics of Rhododendron simsii Under Cadmium Stress - Haochen Di; Ying Liang; Yuting Gong; Songheng Jin; Yanxia Xu (Plants)
Rhododendron simsii (R. simsii), a significant ornamental plant species, is adversely affected by the severe soil heavy metal pollution resulting from rapid industrialization, particularly in terms of its growth environment. Cadmium (Cd), a representative heavy metal pollutant, poses a significant threat to plant growth and photosynthetic physiology. Despite the importance of understanding Cd stress resistance in rhododendrons, research in this area is limited. This study focused on the role of exogenous melatonin (MT) in mitigating Cd-induced stress, emphasizing its impact on photosynthetic physiology. Gas exchange parameters, prompt and delayed fluorescence (DF), 820 nm modulated reflectance (Mr820), and antioxidant enzyme activity, were measured. The findings revealed that under Cd stress, MT-free treatment imposed a more severe limitation on both stomatal and non-stomatal processes in R. simsii leaves, significantly reducing the net photosynthetic rate. In contrast, exogenous MT improved photosynthetic efficiency by increasing the maximum photochemical efficiency of photosystem II, the quantum yield of electron transport, and the photosynthetic performance index. DF and Mr820 analysis demonstrated that MT provided robust protection to both the donor and receptor sides of photosystems I and II. Furthermore, MT significantly decreased malondialdehyde (MDA) content, a marker of oxidative stress, and enhanced the activity of antioxidant enzymes, including superoxide dismutase (SOD) and guaiacol peroxidase (POD). In conclusion, exogenous MT plays a critical role in alleviating Cd-induced stress by enhancing antioxidant defense mechanisms and safeguarding the photosynthetic apparatus, thereby improving the Cd tolerance of R. simsii.